(untitled) (Research, Society and Development, 2020)
Objective: identify the profile of care provided by the Mobile Emergency Care Service to children and adolescents in northwest Paraná. Methodology: a cross-sectional quantitative study was developed in the northwest of the State of Paraná. The sample consisted of all the records of the service team of the Mobile Emergency Service. Data collection took place in the first semester of 2017, data were extracted from the care provided to patients aged between 0 and 19 years. The analysis of associated factors was performed by calculating the odds ratio. Results: 1483 consultations were analyzed, of which 62.2% were adolescents, followed by the age group of infants and children, both representing 14.1%. Conclusion: The calls dealt with transfers, breathing problems, domestic accidents in the vast majority, and the most frequent place of calls was the homes. It was concluded that the strengthening of educational and health institutions is necessary, so that they are prepared to receive this clientele, as well as the importance of spreading the functioning of the Mobile Emergency Care Service, so that it is not used only as a transfer service.